Skutki wprowadzenia euro jako pieniądza międzynarodowego - Borowiec, Jan (The consequences of the euro introduction as an international currency, 2006)
This article concerns the consequences of the euro currency introduction for the European and world markets. Today the euro currency is the second international currencu, so it is very important to understand its different functions. This article also considers the influence on international trade and national economies. There is also mentioned the meaning of the euro currency for financial and monetary markets as the instrument of many transactions. The euro meaning is still more regional than international. The future of euro currencu depends not only on European economy, so international agents must take into account world economy trends in order to take advantages when they use euro instead of dollar.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (13); 2006; nr 1127, s. 25-37